Identification of genes involved in chicken follicle selection by ONT sequencing on granulosa cells - Li, Dandan; Zhong, Conghao; Sun, Yi; Kang, Li; Jiang, Yunliang (Frontiers in Genetics, 2023)
In chickens, follicle selection is an important process affecting laying traits, which is characterized by the differentiation of granulosa cells and the synthesis of progesterone by granulosa cells from hierarchical follicles. By using Oxford Nanopore Technologies (ONT) approach, we compared the transcriptomes of granulosa cells between pre-hierarchical (Pre-GCs) and hierarchical follicles (Post-GCs) to identify genes underlying chicken follicle selection. A total of 2,436 differentially expressed genes (DEGs), 3,852 differentially expressed transcripts (DETs) and 925 differentially expressed lncRNA transcripts were identified between chicken Pre-GCs and Post-GCs. For all of the significant DETs, the alternative 3' splice sites (A3) accounted for a maximum of 23.74% of all alternative splicing events. Three DETs of the 7-dehydrocholesterol reductase gene (DHCR7) named as T1, T3 and T4, differing in 5' untranslated regions (UTRs), increased in Post-GCs with different folds (T1: 1.83, T3: 2.42, T4: 5.06). The expression of the three DHCR7 transcripts was upregulated by estrogen in a dose-dependent manner, while was downregulated by bone morphogenetic protein 15 (BMP15) and transforming growth factor-beta 1 (TGF-β1). Follicle stimulating hormone (FSH) and bone morphogenetic protein 4 (BMP4) promoted the expression of the three DHCR7 transcripts in Pre-GCs at lower concentrations, while repressed their expression at higher concentrations. The data from this study may provide a reference for better understanding of the genetic mechanisms underlying follicle selection in chicken and other poultry species.